Experimental studies and numerical validation of sound insulation of plastic acoustic metamaterial composed of perforated layers and resonators - Naimušin, Andrej; Januševičius, Tomas (International Conference “Environmental Engineering”, 2023)
Noise – messy loud noises of different frequencies, which have various types of pressure, which can be felt as air vibrations or sounds that interfere with human comfort. This kind of noise can be transferred through building construction and/or directly to the human ear. To prevent or minimise noise transfer, sound insulation of considerate construction should be improved. The accumulation of plastic waste and the lack of proper disposal methods has created a critical and unprecedented problem where plastic waste enters our water resources, overflows landfills, leaches into the soil, and enters the air, polluting all natural objects and other resources in our environment. In this research, plastics would be used as secondary raw material to create a better sound insulation solution than what is currently available on the market, such as plasterboard. By applying Circular Economy principles, plastic waste will extend its life cycle and be used as secondary raw material to create metamaterial structures with good sound insulation properties. Numerical validation of metamaterial acoustic characteristics will be compared to the experimental study using an impedance tube.